2022-RA-755-ESGO Comparison of PD-L1 status between primary and paired recurrent/metastatic cervical cancer. (20th October 2022) - Ataseven, Beyhan; Dagres, Timoleon; Heitz, Florian; Concin, Nicole; Thomas, Theresa; Imterat, Majdi; Pauly, Nina; Heikaus, Sebastian; Traut, Alexander; Moubarak, Malak; Harter, Philipp
Abstract : Introduction/Background: Randomized trials established the clinical benefit of PD-1-inhibitors in recurrent/metastatic cervical cancer (CC). However, this benefit seems to be restricted mainly to PD-L1-positiv CC. The purpose of this study was to compare the PD-L1-status in primary CC with a paired sample at the time of recurrent/metastatic disease. Methodology: PD-L1-scoring was analyzed by immunohistochemistry (Ventana PD-L1 (SP263) in archived tumor tissue of primary CC and paired recurrent/metastatic CC (n= 24). PD-L1-positivity was defined as CPS (combined positive score) ≥1. Results: 50% (12/24) of patients were in FIGO stage IB1-IIA2 at primary diagnosis and the majority had squamous cell histology (87.5%; 21/24). Median PFS was 8.9 (95% CI: 7.8–10.0) months.PD-L1-CPS ≥1 was found in 96% (23/24) of primary and 92% (22/24) of paired recurrent/metastatic CC. The median CPS was 22 (range 0–80) in primary and 20 (range 0–90) in recurrent/metastatic CC. Correlation between primary and recurrent/metastatic CC was high (0.79). Only in one case a shift from a CPS-positive primary to CPS-negative relapsed disease was detected. Conclusion: Comparing PD-L1-status (CPS) between primary and recurrent/metastatic CC demonstrated a high concordance. Our data indicate, that PD-L1 testing in archival material from primary tumor is sufficient, if a fresh sample at relapse or of metastases is not available.